Impact of intraoperative packed red blood cell transfusion volume on prognosis in CRS: a propensity-matched study - Li, Jie; Xing, Youzhong; Chen, Wenwen; Sun, Ya (Frontiers in Surgery, 2026)
BackgroundCytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) is an effective treatment for peritoneal metastasis but is associated with significant blood loss requiring intraoperative red blood cell (RBC) transfusion. Evidence suggests transfusions may impair immunity and worsen oncologic outcomes, yet the prognostic impact of intraoperative packed RBC transfusion (iPRBT), especially transfusion volume, in CRS/HIPEC remains unclear.MethodsWe conducted a single-center, retrospective study of 128 patients with advanced peritoneal metastasis who underwent CRS with intraoperative RBC transfusion between January 2018 and December 2024. Patients were stratified into low transfusion (≤4 units) and high transfusion (>4 units) groups. Propensity score matching (PSM) was applied to control for key covariates including CC score, operative time, blood loss, preoperative peritoneal cancer index (PCI), platelet count, age, and gender. Postoperative complications (Clavien–Dindo grade ≥ II) and overall survival (OS) were analyzed.ResultsA total of 128 patients were included, among whom high intraoperative transfusion volume was significantly associated with higher CC score, greater blood loss, longer operative time, elevated preoperative PCI, and lower preoperative platelet counts. After propensity score matching, 48 patients were analyzed. The overall complication rate was 39.6%, with no significant difference between groups (P = 0.768). Hematologic recovery suggested transient improvement of postoperative anemia with higher transfusion volumes. However, long-term survival was significantly reduced in the high transfusion group, with 1-, 3-year OS rates of 42.7%, 18.3%, compared to 74.8%, 62.8%, and 50.2% in the low transfusion group (P = 0.019).ConclusionsHigher iPRBT may ease postoperative anemia but is associated with poorer long-term survival, without a clear link to postoperative complications. These findings support a more restrictive transfusion strategy in CRS/HIPEC.